Enhanced Solar Photoelectrochemical Conversion Efficiency of ZnO:Cu Electrodes for Water-Splitting Application. (19th September 2013) - Dom, Rekha; Baby, Lijin Rose; Kim, Hyun Gyu; Borse, Pramod H.
Abstract : n-type ZnO:Cu photoanodes were fabricated by simple spray pyrolysis deposition technique. Influence of low concentration (range ~10 −4 –10 −1 %) of Cu doping in hexagonal ZnO lattice on its photoelectrochemical performance has been investigated. The doped photoanodes displayed 7-time enhanced conversion efficiencies with respect to their undoped counterpart, as estimated from the photocurrents generated under simulated solar radiation. This is the highest enhancement in the solar conversion efficiency reported so far for the Cu-doped ZnO. This performance is attributed to the red shift in the band gap of the Cu-doped films and is in accordance with the incident-photon-current-conversion efficiency (IPCE) measurements. Electrochemical studies reveal an n-type nature of these photoanodes. Thus, the study indicates a high potential of doped ZnO films for solar energy applications, in purview of the development of simple nanostructuring methodologies.